Boundary controllability of impulsive integrodifferential evolution systems with time-varying delays. Issue 5 (3rd September 2018) - Radhakrishnan, B.; Chandru, P.
ABSTRACT: In this paper, authors studied the boundary controllability results for neutral impulsive integrodifferential evolution systems with time-varying delays in Banach spaces. The sufficient conditions of the boundary controllability are proved under the evolution operator. The results are obtained by using the semigroup theory and the Schaefer fixed point theorems.